2023
DOI: 10.1002/asjc.3043
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive fractional‐order nonsingular fast terminal sliding mode formation control of multiple quadrotor UAVs‐based distributed estimator

Abstract: This paper mainly solves two major problems that are unavoidable in leader–follower formation process of quadrotor UAV group: the existence of external uncertainty disturbance and communication limited between quadrotor unmanned aerial vehicle (UAV) group. To solve the problem that only one of the followers in the leader–follower formation can obtain the leader's information, an improved distributed estimator is proposed in this paper, which can accurately estimate the leader's information for each follower. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In order to mitigate disturbance, a FOC-extended state observer of a Tri-copter UAV was developed in [27]. Furthermore, an adaptive FOCsliding mode formation control of a multiple quadrotor UAV-based distributed estimator was developed in [28]. The authors in [29] proposed a robust formation tracking problem for a heterogeneous multi-robot system with FOC, consisting of UAVs and unmanned surface vehicles (USVs), to handle multiple disturbances.…”
Section: Modeling and Control Of Uavsmentioning
confidence: 99%
“…In order to mitigate disturbance, a FOC-extended state observer of a Tri-copter UAV was developed in [27]. Furthermore, an adaptive FOCsliding mode formation control of a multiple quadrotor UAV-based distributed estimator was developed in [28]. The authors in [29] proposed a robust formation tracking problem for a heterogeneous multi-robot system with FOC, consisting of UAVs and unmanned surface vehicles (USVs), to handle multiple disturbances.…”
Section: Modeling and Control Of Uavsmentioning
confidence: 99%
“…Sampled-data control (SDC) has important applications in digital technology, aerospace, and signal transmission [18]. The term SDC refers to the process in which the continuous-time input signal is sampled and quantized by a digital computer to generate a discrete-time input signal, which eventually reverts to a continuous-time input signal through the action of a zero-order holder (ZOH) [19][20][21]. In the sampling control system, it has been observed that as the sampling interval increases, there is a corresponding reduction in communication channel occupancy, a decrease in controller drive load, and a decrease in signal transmission [22,23].…”
Section: Introductionmentioning
confidence: 99%